2017
DOI: 10.1007/978-1-4939-7240-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic di-GMP-Responsive Transcriptional Reporter Bioassays in Pseudomonas aeruginosa

Abstract: 3',5'-cyclic diguanosine monophosphate (cyclic di-GMP) is a bacterial secondary messenger molecule that regulates many important cellular activities and behaviors, such as motility and biofilm formation. While mass spectrometry protocols for quantitative analyses of intracellular cyclic di-GMP concentrations have been developed, they are time intensive, expensive, low-throughput, and incapable of directly monitoring dynamic changes in vivo. In this protocol, we provide a Pseudomonas aeruginosa-specific detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This c-di-GMPresponsive reporter is a transcriptional fusion of the cdrA promoter with the gene encoding luciferase and enables real-time evaluation of c-di-GMP-regulated activities through the quantification of luminescence. c-di-GMP reporters utilizing this transcriptional fusion-based approach were previously published and validated (27)(28)(29)(30). In a swarming assay, the wt harboring P cdrA ::lux showed minimal luminescence 3 h after inoculation on surfaces (i.e., after sufficient time for the transition to a swarming mode) for all media tested, which is expected for motile bacteria (Fig.…”
Section: Figmentioning
confidence: 81%
See 1 more Smart Citation
“…This c-di-GMPresponsive reporter is a transcriptional fusion of the cdrA promoter with the gene encoding luciferase and enables real-time evaluation of c-di-GMP-regulated activities through the quantification of luminescence. c-di-GMP reporters utilizing this transcriptional fusion-based approach were previously published and validated (27)(28)(29)(30). In a swarming assay, the wt harboring P cdrA ::lux showed minimal luminescence 3 h after inoculation on surfaces (i.e., after sufficient time for the transition to a swarming mode) for all media tested, which is expected for motile bacteria (Fig.…”
Section: Figmentioning
confidence: 81%
“…After detailing the divergence in ΔdipA mutant swarm phenotypes on several medium conditions, we were curious whether the mutant was simply producing less c-di-GMP on rich media and more c-di-GMP on minimal media. We utilized a P cdrA ::lux reporter (27) to assess c-di-GMP production levels on LB Lennox broth, lab-mixed LB (tryptone, yeast extract, and NaCl), and M8-glucose-Casamino Acids medium and FAB-glutamate. This c-di-GMPresponsive reporter is a transcriptional fusion of the cdrA promoter with the gene encoding luciferase and enables real-time evaluation of c-di-GMP-regulated activities through the quantification of luminescence.…”
Section: Figmentioning
confidence: 99%
“…2b). Additionally, a bioreporter system, which is comprised of a plasmid-borne fusion between the cdrA promoter (P cdrA ) and the gene for green fluorescent protein (gfp) 49 , indicated that cdrA transcription in a PAO1 strain bearing tdcA increased linearly 5.2-fold from 31 to 41°C (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…This organism was engineered to express tdcA (or the inactive tdcA 162ΔG allele) via site-directed transposon mutagenesis 56 . Subsequently, these strains were transformed with a luminescent c-di-GMP bioreporter, comprised of a fusion between P cdrA and the luxCDABE operon 49 . These transformants were then grown side-by-side in Petri dishes at 25°C, then shifted to 37°C and photographed in the dark via time-lapse imaging.…”
Section: Resultsmentioning
confidence: 99%
“…We also evaluated the activity of these genes using a heterologous approach to evaluate the effect on c-di-GMP signaling mediated phenotypes in Pseudomonas aeruginosa PAO1 (20)(21)(22). Inducible expression of cdpA or cdpA-I2285 in either P. Mapping residues important for activity in CdpA, I2285, and II2523.…”
Section: E)mentioning
confidence: 99%